Ultrasound-guided glenohumeral joint injections for shoulder pain in ALS: A case series - Burke, Katherine M.; Ellrodt, Amy S.; Joslin, Benjamin C.; Sanpitak, Pia P.; MacAdam, Claire; Deo, Prabhav; Ozment, Kevin; Shea, Cristina; Johnson, Stephen A.; Ho, Doreen; Chu, Samuel K.; Babu, Ashwin N.; et al. (Frontiers in Neurology, 2023)
Introduction Shoulder pain is a common secondary impairment for people living with ALS (PALS). Decreased range of motion (ROM) from weakness can lead to shoulder pathology, which can result in debilitating pain. Shoulder pain may limit PALS from participating in activities of daily living and may have a negative impact on their quality of life. This case series explores the efficacy of glenohumeral joint injections for the management of shoulder pain due to adhesive capsulitis in PALS. Methods People living with ALS and shoulder pain were referred to sports medicine-certified physiatrists for diagnostic evaluation and management. They completed the Revised ALS Functional Rating Scale and a questionnaire asking about their pain levels and how it impacts sleep, function, and quality of life at baseline pre-injection, 1-week post-injection, 1 month post-injection, and 3 months post-injection. Results We present five cases of PALS who were diagnosed with adhesive capsulitis and underwent glenohumeral joint injections. Though only one PALS reported complete symptom resolution, all had at least partial symptomatic improvement during the observation period. No complications were observed. Conclusions People living with ALS require a comprehensive plan to manage shoulder pain. Glenohumeral joint injections are safe and effective for adhesive capsulitis in PALS, but alone may not completely resolve shoulder pain. Additional therapies to improve ROM and reduce pain should be considered.